Culinary Infrastructure: How Facilities and Technologies Create Value and Meaning around Food. Issue 2 (2nd July 2016) - Pilcher, Jeffrey M.
Abstract: Culinary infrastructure comprises the diverse artifacts, organizations, and media that mobilize food or that organize and convey knowledge about food, thereby facilitating production and consumption, but without having those transformations as a direct goal. This infrastructure includes both material components (such as transportation and sewage networks, marketplaces and ports, refrigeration, and communication technologies) and immaterial or embodied expressions of knowledge (recipes and cooking practices, futures markets and intellectual property, quality certifications and health regulations). Although failures of infrastructure become apparent in the form of supply shortages or food contamination, the indirect consequences of infrastructure can be just as important in shaping the kinds of foods that are available to consumers and who will profit from the sale of those foods. By surveying a diverse variety of infrastructural nodes and linkages, this essay seeks to overcome fundamental divisions within the interdisciplinary field of food studies between economic and ecological dimensions of food supply and the social and cultural meanings within which they are embedded. Historical analysis of the technological and knowledge-based systems of infrastructure can also highlight both the imperial origins of industrial food production and the contingent and contested nature of food systems. The essay gives particular attention to struggles over the boundaries between public and private control of infrastructure.